แบบจำลองทางคณิตศาสตร์ของภาพถ่ายสเปคสำหรับการประเมินโรคลมชัก - กิติวัฒน์ คำวัน (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Epilepsy is a neurological disorder caused by electrical abnormalities in brain, causing seizures or unusual behavior. The powerful functional imaging tool as Single Photon Emission Computed Tomography (SPECT) has dramatically changed the approach for epilepsy evaluation. In this study, we developed a kinetic model of 99mTc-ECD absorption in brain, depending on the acquiring time of patients with epilepsy. Fifthteen retrospective epilepsy patient data underwent 99mTc-ECD SPECT imaging at Division of Nuclear Medicine, King Chulalongkorn Memorial Hospital were collected, then adjusted for kinetic parameters and numerical methods were used to find the solution of the kinetic model to compare data from SPECT imaging, specifications, and relative error to get the appropriate parameters for patients with epilepsy. The epileptic patients had absorption around 27.9084 MBq/ml. From SPECT imaging, the essential parameter of 99mTc-ECD absorption model are kinject = 0.089±0.0555, K₁ = 0.25±0.0732, k₂ = 0.24±0.0229, k₃ = 0.53±0.0254, k₄= 0 and kout = 0.00688±0.0055. We have concluded that these parameters could describe the kinetics of 99mTc-ECD absorption in the brains of epileptic patients. It is also a developmental paradigm in which physicians can pinpoint the origin of the seizure more precisely.